La conformación intersubjetiva de la libertad: un análisis de la influencia de Fichte en la filosofía de Kierkegaard - Rodríguez, Pablo Uriel (ARFIL y UNL, 2019)
Kierkegaard´s thought was strongly influenced by German idealist philosophers. While the scholars have studied the philosophical link between Hegel (or Schelling) and the danish, Kierkegaard´s relation with Fichte remained silent. The purpose of this article is to develop a new perspective on the Fichte-Kierkegaard relationship. First, we explore Kierkegaard´s readings on Fichte’s system. Second, we discuss the new global interpretations of Kierkegaard’s philosophy and the place of Fichte in these interpretations. Third we show that Fichte’s concept of Aufforderung is on the ground of the self’s theory that Kierkegaard exposes in his latest books.